The Correlation Between Translanguaging Strategy and Reading Comprehension of Tenth Grade Students at SMA Negeri 2 Tabanan - I Gusti Agung Ayu Eka Pratiwi; Ni Wayan Satri Adnyani; Putu Santi Oktarina (Indo Publishing, 2026)
The purpose of this study is to examine the correlation between translanguaging strategy and reading comprehension of tenth grade students at SMA Negeri 2 Tabanan. This study employed a correlational research design. The participants consisted of 35 tenth grade students selected through purposive sampling. Data were collected using two instruments, namely a reading comprehension test consisting of 25 multiple-choice questions and a translanguaging strategy questionnaire with 15 Likert scale statements. The data were analyzed using descriptive and inferential analysis, which included normality test, linearity test, and Spearman’s Rank correlational test. The findings of this research show that there is no significant correlation between translanguaging strategy and students’ reading comprehension. This is indicated by the significance value of 0.786, which is higher than 0.05. The absence of such a correlation is due to a difference in pattern between the use of translanguaging strategies and students’ reading comprehension scores. These findings suggest that translanguaging strategy do not always align with students’ reading comprehension and are not necessarily the primary factor influencing it. Therefore, students, teachers, and schools are advised to implement various learning strategies, particularly in reading activities tailored to learning needs. Future research is suggested to examine other factors influencing students’ reading comprehension, using more diverse research instruments, and involving a broader sample and research context.